2020
DOI: 10.5296/ber.v10i2.17046
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility during the Coronavirus Pandemic: An Interim Overview

Abstract: The Coronavirus outbreak caught the world by surprise, spreading like wildfire and causing fatal illness to many. The ongoing pandemic and its implications have led to severe global socioeconomic disruption, halting most regular activities. Coping with the pandemic and its horrible consequences required to pull together all resources and unite efforts by individuals, organizations and governments. Businesses have embarked on an effort to support coping with the pandemic in various ways, as aligned with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…The third is Bank Mandiri and BRI's responsive attitudes and actions in the face of new norms in various CSR programs. Forms of corporate social responsibility to the community can include various aspects as giving charity to the community, giving in the form of goods from the company's products and services that need it, or using facilities or managerial expertise that helps those in need, and more [16]. Bank Mandiri and BRI have carried out these activities significantly, especially those related to the coronavirus pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…The third is Bank Mandiri and BRI's responsive attitudes and actions in the face of new norms in various CSR programs. Forms of corporate social responsibility to the community can include various aspects as giving charity to the community, giving in the form of goods from the company's products and services that need it, or using facilities or managerial expertise that helps those in need, and more [16]. Bank Mandiri and BRI have carried out these activities significantly, especially those related to the coronavirus pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, (He & Harris, 2020) believe that the Covid-19 pandemic has also created opportunities for businesses to successfully implement CSR initiatives that will benefit the local community immensely. During the pandemic era, entrepreneurs have taken several different measures to mitigate the effects of the pandemic (Marom & Lussier, 2020). In this context, (Kantor & Kubiczek, 2021) observed that in Poland, one of the solutions for the lockdown of cultural institutions revolved around the activities that were undertaken for the benefit of the local community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizations and companies have put in their efforts and resources to deal with the consequences of the pandemic, guided by the concept of their social responsibility. The range of CSR practices in the face of a serious global crisis allowed for deepening the understanding and insight into the best ways in which companies should plan and practice their social responsibility (Marom & Lussier, 2020 ). In this case, the verification of crisis management strategies seems important, important for the public relations industry and the structure of the offer of qualified services in this area.…”
Section: The Need To Implement Csr In the Age Of A Pandemicmentioning
confidence: 99%